2021
DOI: 10.1155/2021/5552743
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Analyzing Deep Learning and Transfer Learning Approaches for Health Monitoring

Abstract: With the rise and advancement of technology, early detection and involvement in health-associated monitoring through home control are growing with population aging. The expansion of healthy life expectations is progressively significant due to the speedy aging of the world population. The patient requires early and home-based treatment to detect and prevent disease on time and with less effort. Home-based health monitoring has been considered the need of a smart home. The services of health monitoring can faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Health data are useful in many ways when processed intelligently [ 4 , 5 ]. The intelligent processing of health data may help to prevent pandemic outbreaks in a city, states, or countries, helping to identify acute diseases such as Alzheimer's disease, diabetes, cardiovascular diseases, and lung cancer [ 6 ]. Blockchain is more reliable and robust as once the data are created, it can only be read and not edited or updated.…”
Section: Introductionmentioning
confidence: 99%
“…Health data are useful in many ways when processed intelligently [ 4 , 5 ]. The intelligent processing of health data may help to prevent pandemic outbreaks in a city, states, or countries, helping to identify acute diseases such as Alzheimer's disease, diabetes, cardiovascular diseases, and lung cancer [ 6 ]. Blockchain is more reliable and robust as once the data are created, it can only be read and not edited or updated.…”
Section: Introductionmentioning
confidence: 99%
“…Experts believe that deep learning will facilitate medical studies in the coming years of medicine. The successes obtained in the works [ 23 – 30 ] on the subject support this idea; it is about the improvement, classification, segmentation, and detection of medical images and related to the images and taking vital precautions. Moreover, Limwattanayingyong et al showed that DL was more successful when they compared sight-threatening DR (STDR) screening with educated human grading and DL grading [ 31 ].…”
Section: Introductionmentioning
confidence: 88%
“…Up to now, there are some articles dedicated to presenting the state of the art of transfer learning-motivated FD methods, such as the survey papers [60], [94], [95]. Retrospecting the development of transfer learning-motivated FD approaches, it is not difficult to find an intimate relationship between deep learning and transfer learning.…”
Section: Developments Of Transfer Learning-based Fdmentioning
confidence: 99%